Comparing the Impact of Workload on the Mental Health of House Officers at Public and Private Hospitals of Peshawar : House Officers Workload and Mental Health - Zia, Aiman; Ali, Zobia; Khan, Farzeen; Imran, Rafia; Zubair, Fareeha; Sajjad, Maha; Ishfaq, Hamayl (Pakistan Journal of Health Sciences, 2024)
Healthcare environments place a high priority on the mental health of medical personnel, especially house officers. Objective: To compare the impact of workload on the mental health of house officers at public and private hospitals of Peshawar. Methods: Descriptive cross-sectional design was used to gather data from 164 house officers at four major hospitals in Peshawar, Pakistan (Khyber Teaching Hospital, Hayatabad Medical Complex, Kuwait Teaching Hospital, and Northwest General Hospital). In order to investigate the relationships between workload and mental health, data gathered from October 2023 to February 2024 via a standardized questionnaire on demographics, mental health, and workload was analyzed using descriptive statistics as well as inferential tests like chi-square and t-tests. Results: Out of 164 hospital patients, 29.7% had ages between 26 and 28. Among them 41.8% were female and 57.6% were male. Surgery (44.8%) and Medicine (54.5%) were the departments’ representatives, while General Surgery (34.5%), Medicine (36.4%), Eye (15.2%), and ENT (13.3%) were the wards. The mean scores were (public: 30.69, private: 28.76; p-value.345), patient distribution (public: 11-40, private: 0-40; p-value 0.008), shift distribution (public: 0-15, private: 0-10), and self-reported concentration levels (p-value 0.051) showed significant differences between public and private hospitals. However, there was no discernible fluctuation in the strain levels (p-value = 0.658). Conclusions: House officers in Peshawar need special assistance from all sectors because of their tremendous responsibilities, particularly in public hospitals.